A multi-criteria methodology to evaluate the optimal location of a multifunctional railway portal on the railway network. Issue 2 (August 2015) - Bersani, Chiara; Guerisoli, Claudio; Mazzino, Nadia; Sacile, Roberto; Sallak, Mohamed
Highlights Multifunctional railway portals improves safety of a railway infrastructure. TCCS monitors real time convoys transits, to detect specific faults. Proposed AHP approach evaluates locations to install a TCCS on a railway sections. Main criteria to assess ranking of eligible sites-Track layout, safety, technical feat.